2013
DOI: 10.1088/1674-1137/37/9/098003
|View full text |Cite
|
Sign up to set email alerts
|

Study of high pressure structural stability of CeO 2 nanoparticles

Abstract: Abstract:In situ high pressure XRD diffraction and Raman spectroscopy have been performed on 12 nm CeO 2 nanoparticles. Surprisingly, under quasihydrostatic condition, 12 nm CeO 2 nanoparticles maintain the fluorite-type structure in the whole pressure range (0-51 GPa) during the experiments, much more stable than the bulk counterpart (P T ~31 GPa). In contrast, they experienced phase transition at pressure as low as 26 GPa under non-hydrostatic condition (adopting CsCl as pressure medium). Additionally, 32-36… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…The differences in the transition pressures at which the structural transitions occur may depend on the nature of the starting materials and the experimental conditions. Considering the detection methods of the determination of the grain size, this work along with a reanalysis of previous studies on nc CeO 2 5 6 7 10 11 14 16 allow us to reach consistency among several studies of the size dependence of the phase transitions, that is the nanocrystals exhibit elevated phase transition pressures as compared to bulk materials 6 14 17 . This may due to the initial peak broadenings of nanosized starting material and progressive broadening and intensity reduction of the reflections which result from the increasing pressure.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The differences in the transition pressures at which the structural transitions occur may depend on the nature of the starting materials and the experimental conditions. Considering the detection methods of the determination of the grain size, this work along with a reanalysis of previous studies on nc CeO 2 5 6 7 10 11 14 16 allow us to reach consistency among several studies of the size dependence of the phase transitions, that is the nanocrystals exhibit elevated phase transition pressures as compared to bulk materials 6 14 17 . This may due to the initial peak broadenings of nanosized starting material and progressive broadening and intensity reduction of the reflections which result from the increasing pressure.…”
Section: Resultsmentioning
confidence: 73%
“…Due to its promising technological applications, numerous investigations have been reported on the structure stabilities and compressibility of different sized CeO 2 under high pressure5678910111213. It is reported that the phase transformation pressure of nanosized CeO 2 decreased compared to that of bulk counterpart89, whereas other studies hinted that nano-CeO 2 remains stable to much higher pressures than the bulk7101114. Moreover, an anomalous compressive behavior of CeO 2 nanocubes, which is due to the strengthening of the surface Ce-O bonds, was observed by Ge et al 5.…”
mentioning
confidence: 99%
“…13,14 Based on this, photonic nanojets have been studied using different properties of the dielectric structure such as non-spherical nanoparticles 15 and also graded index concepts have been applied. 16,17 Besides, experimental demonstration of the backscattering enhancement generated by photonic jets at microwave frequencies has been reported. 18 In this paper, a new mechanism to produce jets is numerically demonstrated using 3D dielectric cuboids (hexahedrons) working at sub-THZ and THz frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, Chinese is treated as an S‐framed language with intra‐typological variation, in which manner is typically encoded via a manner verb and path via DCs, but there are also situations where DCs are used as full path verbs showing V‐framed possibility. The rationale for this is that analyzing the constituents as DCs rather than full verbs is widely accepted in many canonical Chinese grammar books (e.g., Chao, ; Cheung, Liu, & Shih, ; Liu, Pan, & Gu, ), as well as many popular Chinese language textbooks (e.g., He et al., ; Liu & Yao, ; Wu et al., ), including the textbooks used in the university where the data were collected.…”
Section: Introductionmentioning
confidence: 99%
“…He‐take‐out‐Perf.‐one‐Cl.‐book”) is supplied in the sentence, the deictic path 来 lái ‘hither’ or 去 qù ‘thither’ can be omitted (cf. Liu & Yao, ).…”
mentioning
confidence: 99%